Telomeres and a repeat‐rich chromosome encode effector gene clusters in plant pathogenic Colletotrichum fungi. (12th April 2021) - Gan, Pamela; Hiroyama, Ryoko; Tsushima, Ayako; Masuda, Sachiko; Shibata, Arisa; Ueno, Akiko; Kumakura, Naoyoshi; Narusaka, Mari; Hoat, Trinh Xuan; Narusaka, Yoshihiro; Takano, Yoshitaka; Shirasu, Ken
Summary: Members of the Colletotrichum gloeosporioides species complex are causal agents of anthracnose in many commercially important plants. Closely related strains have different levels of pathogenicity on hosts despite their close phylogenetic relationship. To gain insight into the genetics underlying these differences, we generated and annotated whole‐genome assemblies of multiple isolates of C . fructicola ( Cf ) and C . siamense ( Cs ), as well as three previously unsequenced species, C . aenigma ( Ca ), C . tropicale and C . viniferum with different pathogenicity on strawberry. Based on comparative genomics, we identified accessory regions with a high degree of conservation in strawberry‐pathogenic Cf, Cs and Ca strains. These regions encode homologs of pathogenicity‐related genes known as effectors, organized in syntenic gene clusters, with copy number variations in different strains of Cf, Cs and Ca . Analysis of highly contiguous assemblies of Cf, Cs and Ca revealed the association of related accessory effector gene clusters with telomeres and repeat‐rich chromosomes and provided evidence of exchange between these two genomic compartments. In addition, expression analysis indicated that orthologues in syntenic gene clusters showed a tendency for correlated gene expression during infection. These data provide insight into mechanisms by which Colletotrichum genomes evolve, acquire and organize effectors.